2010
DOI: 10.1103/physrevlett.104.208501
|View full text |Cite|
|
Sign up to set email alerts
|

Thermal Conductivity of Periclase (MgO) from First Principles

Abstract: We combine first-principles calculations of forces with the direct nonequilibrium molecular dynamics method to determine the lattice thermal conductivity k of periclase (MgO) up to conditions representative of the Earth's core-mantle boundary (136 GPa, 4100 K). We predict the logarithmic density derivative a ¼ ð@ lnk=@ ln Þ T ¼ 4:6 AE 1:2 and that k ¼ 20 AE 5 Wm À1 K À1 at the core-mantle boundary, while also finding good agreement with extant experimental data at much lower pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 31 publications
6
103
1
1
Order By: Relevance
“…for the oxide phases (Debye theory; 19,20), and for the perovskite phases (modified Debye theory; 13,22). K 0 T is the pressure derivative of the isothermal bulk modulus, γ the Grüneisen parameter, and q ¼ −ð∂ ln γ∕∂ ln ρÞ T .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…for the oxide phases (Debye theory; 19,20), and for the perovskite phases (modified Debye theory; 13,22). K 0 T is the pressure derivative of the isothermal bulk modulus, γ the Grüneisen parameter, and q ¼ −ð∂ ln γ∕∂ ln ρÞ T .…”
Section: Resultsmentioning
confidence: 99%
“…Recent first-principles computations of lattice k in MgO periclase has shown that Debye theory (Eq. 2, see below) gives an excellent representation of the density dependence of k in a simple oxide (19)(20)(21), while a recent set of experimental measurements (22) indicates that the density dependence of k in more complex solids can be represented by removing the assumption that the phonon group velocities are proportional to the Debye temperature (13; Eq. 3, see below).…”
mentioning
confidence: 99%
“…Recent technical progress both in the experiment and the theoretical calculation enables us to reveal high-pressure and high-temperature behavior of lattice thermal diffusivity (and conductivity) of lower mantle minerals, MgSiO 3 perovskite and MgO periclase (de Koker 2010;Stackhouse et al 2010;Tang and Dong 2010;Manthilake et al 2011;Haigis et al 2012;Ohta et al 2012;Dekura et al 2013). However, there is only one report regarding the effect of chemical impurity on the lattice conductivity of the lower mantle minerals (Manthilake et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, there has been a great deal of experimental and theoretical activity in determining heat transport properties of the mantle minerals123456 as these parameters have been realized to be critically important for geomodels aiming to better understand the Earth's thermal history and geodynamics789. Central to this knowledge is the determination of various energy contributions to the Earth's overall energy balance.…”
mentioning
confidence: 99%
“…The experimental determinations of the lattice thermal conductivities of these materials are numerous1512131415, but limited in pressure and temperature and also in experimental accuracy. Thus, estimates of the thermal conductivity at the conditions of the CMB are based on phenomenological extrapolations1617 and on theoretical first-principle calculations124181920, both of which are not validated experimentally. Moreover, since the major mantle minerals are solid solutions and have mass disorder, their thermal conductivity is greatly affected21.…”
mentioning
confidence: 99%